2005
DOI: 10.1007/s10789-005-0195-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Deposition and Properties of Silicon Carbonitride Films

Abstract: A variety of advanced analytical techniques were used to characterize silicon carbonitride films grown from new volatile nitrogen-rich silyl derivatives of asymmetrical dimethylhydrazine: (CH 3 ) 2 HSiNHN(CH 3 ) 2 (DMDMSH) and Me 2 Si(NHNMe 2 ) 2 (bisDMHDMS). The results demonstrate that the films contain only Si-C, Si-N, and C( sp 3 )-N bonds, in relative amounts that depend on the molecular structure of the precursor and deposition conditions. The Si-C/[Si-N + C( sp 3 )-N] ratio is considerably larger in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In regard to the behavior of optical energy band gap, Table II shows that E g decreases between S1 and S3, and then increases, where a minimum occurs in sample S3. The values are in the range of the reported ones in the literature [7,17], which fall in the range 2-5 eV. The decrease of E g can be attributed to the increase of the dangling bonds created in the film during the deposition process [11].…”
Section: Optical Properties 321 Optical Constantssupporting
confidence: 62%
See 1 more Smart Citation
“…In regard to the behavior of optical energy band gap, Table II shows that E g decreases between S1 and S3, and then increases, where a minimum occurs in sample S3. The values are in the range of the reported ones in the literature [7,17], which fall in the range 2-5 eV. The decrease of E g can be attributed to the increase of the dangling bonds created in the film during the deposition process [11].…”
Section: Optical Properties 321 Optical Constantssupporting
confidence: 62%
“…13 Ω cm, and dielectric constant of about 2.8) suggest that such films are candidate materials for a number of advanced technological applications, in particular as interlevel insulators with a low permittivity coefficient for next-generation giga-and terabit silicon memory circuits [17].…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Studies [24][25] have been reported that thin-films of silicon carbonitride were synthesized by silicon derivatives of UDMH ((CH 3 ) 2 HSiNHN(CH 3 ) 2 (DMDMSH),(CH 3 ) 2 Si[NHN(CH 3 ) 2 ] 2 (D M-bis-DMHS)) using method of remote-plasma chemical vapor deposition(RPCVD). The ratio of N Si determined the structure of the films.…”
Section: A Inorganic Silicon Derivativesmentioning
confidence: 99%